Autoimmune disorders of the neuromuscular junction. - Lang, B; Vincent, A (2009)
The neuromuscular junction lies beyond the protection of the blood-brain barrier and is particularly vulnerable to antibody-mediated attack. In myasthenia gravis, the expression of acetylcholine receptors (AChRs) in the thymus is under the control of the autoimmune regulator protein (AIRE), and polymorphisms in the AChR correlate with early onset of disease. In some 'AChR seronegative' patients, thymic abnormalities associated with complement-activating antibodies binding only clustered AChRs have been demonstrated, and in others anti-muscle-specific kinase (MuSK) antibodies that show pathogenic effects in vivo. In Guillain-Barré syndrome, newly described antibodies bind to complex gangliosides. General immunosuppression is still the main treatment, but novel treatments that reduce complement-mediated damage or inhibit the binding of pathogenic antibodies are beginning to look promising.